Discovery of the α-emitting isotope 210Pa - M. M. Zhang; J. G. Wang; L. Ma; Z. G. Gan; Z. Y. Zhang; M. H. Huang; H. B. Yang; C. L. Yang; A. N. Andreyev; C. X. Yuan; Y. L. Tian; Y. S. Wang; et al. (Nature Communications)
Abstract Synthesizing isotopes located far away from the line of β-stability is the core research topic in nuclear physics. However, it remains a challenge due to their tiny production cross sections and short half-lives. Here, we report on the observation of a very neutron-deficient isotope 210Pa produced via the fusion-evaporation reaction 175Lu(40Ca, 5n)210Pa at a newly constructed China Accelerator Facility for Superheavy Elements. The measured α-particle energy of E α = 8284(15) keV and half-life of $${T}_{1/2}=6.{0}_{-1.1}^{+1.5}$$ T 1 / 2 = 6 . 0 − 1.1 + 1.5 ms of 210Pa allow us to extend the α-decay systematics and test the predictive power of theoretical models for heavy nuclei near the proton drip line. Based on its unhindered α-decay character, the spin and parity of 210Pa is proposed to be (3+), supported by the large-scale shell model and cranked shell model calculations. This isotope is discovered with substantial statics within  ∼ 3 days using intensive 2 pμA beam, demonstrating the tremendous capability of the facility for the study of heavy and superheavy nuclei.